Cytoplasmic Dynein Is Required for Distinct Aspects of Mtoc Positioning, Including Centrosome Separation, in the One Cell Stage Caenorhabditis elegans Embryo - Gönczy, Pierre (The Rockefeller University Press, 1999)
We have investigated the role of cytoplasmic dynein in microtubule organizing center (MTOC) positioning using RNA-mediated interference (RNAi) in Caenorhabditis elegans to deplete the product of the dynein heavy chain gene dhc-1. Analysis with time-lapse differential interference contrast microscopy and indirect immunofluorescence revealed that pronuclear migration and centrosome separation failed in one cell stage dhc-1 (RNAi) embryos. These phenotypes were also observed when the dynactin components p50/dynamitin or p150(Glued) were depleted with RNAi. Moreover, in 15% of dhc-1 (RNAi) embryos, centrosomes failed to remain in proximity of the male pronucleus. When dynein heavy chain function was diminished only partially with RNAi, centrosome separation took place, but orientation of the mitotic spindle was defective. Therefore, cytoplasmic dynein is required for multiple aspects of MTOC positioning in the one cell stage C. elegans embryo. In conjunction with our observation of cytoplasmic dynein distribution at the periphery of nuclei, these results lead us to propose a mechanism in which cytoplasmic dynein anchored on the nucleus drives centrosome separation.